2011
DOI: 10.1177/1049732311417728
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Fatosphere in Fat Adults’ Responses to Obesity Stigma

Abstract: Obese adults face pervasive and repeated weight-based stigma. Few researchers have explored how obese individuals proactively respond to stigma outside of a dominant weight-loss framework. Using a grounded theory approach, we explored the experiences of 44 bloggers within the Fatosphere--an online fat-acceptance community. We investigated participants' pathways into the Fatosphere, how they responded to and interacted with stigma, and how they described the impact of fat acceptance on their health and well-bei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
82
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(84 citation statements)
references
References 50 publications
0
82
1
1
Order By: Relevance
“…There exist supportive online communities that provide compassionate, nonjudgmental spaces for individuals to share weight-related experiences and efforts. Over time, these interactions may improve self-esteem and resilience to stigma [5,15,22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There exist supportive online communities that provide compassionate, nonjudgmental spaces for individuals to share weight-related experiences and efforts. Over time, these interactions may improve self-esteem and resilience to stigma [5,15,22].…”
Section: Discussionmentioning
confidence: 99%
“…Supportoriented blogs and forums are health-promoting communities that offer a safe place where members' bodies are accepted, and allow participants to understand, negotiate, and, at times, reject the marginalized identity ascribed to them in their offline environment [38]. This type of supportive dialogue can be empowering [5]. As such, social media must not be viewed simply as breeding grounds for weight stigma, but also environments that can insulate overweight individuals from stigma.…”
Section: Positive Sentimentmentioning
confidence: 99%
“…Research on fatosphere blogs has found that users connect over the common experience of feeling uncomfortable about one's body at an early age (Dickins et al, 2011). Members of the fat acceptance community may also characterize themselves as having similar beliefs regarding social norms and stigmatization.…”
Section: Social Identity and Body Imagementioning
confidence: 99%
“…An outsider would be someone who has internalized the stigma that being fat is unhealthy and socially undesirable. For example, fatosphere blog communities will automatically remove any content that indicates self-loathing messages (Dickins et al, 2011). An outsider of this community would be someone who succumbs to ideologies surrounding being overweight and being unhealthy (Anderson, 2012;Campos, 2005;Ernsberger & Haskew, 1997;Harding, 2007;Satinsky & Ingraham, 2014).…”
Section: Social Identity and Body Imagementioning
confidence: 99%
See 1 more Smart Citation